Coalition-driven initiatives in the Ugandan dairy sector: Elites, conflict, and bargaining - Anne Mette Kjær; Fred Muhumuza; Tom Mwebaze (Danish Institute for International Studies (DIIS), 2012)
The dairy sector is one of the only agricultural sectors in Uganda that has enjoyed sustained high growth since the late 1980s. Milk and the cold dairy chain developed especially in the south-western part of the country. This paper explains why this is so by the sector's relation to the ruling coalition. We argue that the dairy sector was relatively successful because the south-western based ruling elite wanted to build a support base in its home area. In addition, the elite had a special interest in dairy since key elite members owned dairy cattle themselves. As milk production grew, the ruling elite wanted to regulate the sector as this would help the big processor, the state owned and later privatized Dairy Corporation. Regulation was relatively successful and a pocket of bureaucratic efficiency was established in an agency called the Dairy Development Authority. The reason why regulation was enforced to a considerable extent was the organization of dairy farmers and traders and the bargaining and compromise with the Dairy Development Authority this organization of industry actors enabled.
Keywords: 300; Milchviehhaltung; Milchverarbeitung; Patronage; Uganda